ACCOUNTANCY UNDER ECONOMIC SELF-GOVERNMENT. (The Accounting Review, 1933)
Abstract The article focuses on accountancy under economic self government. There is general discontent with the economic system, with the political system, and with the relation between the two. There is also general aversion to political and bureaucratic government interference in economic affairs. A National Economic Council is often proposed. But usually this council is conceived as a superstructure to be imposed upon the existing national economy. A National Economic Council to fit the American idea therefore should receive its powers, duties and responsibilities from the business system which it would represent. Such a body would not be a revolutionary proposal; it is modeled upon the system long accepted by the American people in political matters. Through the channels of this organization accounting information would flow from the business enterprises, through the institutes and federations of accounting, to the National Economic Council, particularly its Division of Accounts. This information would provide the basis of a national economic balance sheet and economic budget plan.